PARADIGMA BARU MENYEDIAKAN TENAGA KERJA YANG DIDASARKAN PADA KEBIJAKAN SISTEM PENDIDIKAN NASIONAL: SEBUAH ANALISIS KEBIJAKAN - Erman Suparno (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2015)
The research is to analyze the interlinking between national education system and manpower policies from the view of manpower preparation. This research is a desk study applying policy analysis, which was conducted through intensive and comprehensive understanding process against education and manpower, including other related existing policies, coming up with policy recommendation of a new strategy in preparing manpower. Data was collected using documentation and literature study concerning education and manpower policies, including other relevant literatures. The main results of this research are: (1) the act Number 20 year 2003 concerning National education System interlink with the act Number 13 year 2003 concerning manpower, in which the non-formal education is channeled through training institutional, then implemented as vocational training institution operated by the government or private sector; (2) The National Education Ministerial Regulation Number 23 year 2006 concerning competency Standard for Elementary and secondary Education level interlinks with the Act Number 13 year 2003 concerning manpower, in which vocational training shall consider labor market demand and business, in accordance with working standard competency. In fact, this has not been widely implemented, as high number of graduates from vacation education institutions still cannot enter to the world of work, because of mismatching to the required competency; (3) to recommend a strategy of manpower preparation, which is a new paradigm, in integrating training, certification and placement programs (Three in One Program). The research’s findings conclude that the new paradigm of manpower preparation based on National Education System Policy, would lead in producing competent manpower, which fits with business needs and labor market, therefore, it reduces unemployment and alleviates poverty.